Bacterial blood microbiome of Mastomys rodents: implications for disease spill-over at the animal-human interface within the Bushbuckridge-East community, South Africa - Agatha O. Kolo; Agatha O. Kolo; Kelly A. Brayton; Kelly A. Brayton; Nicola E. Collins; Armanda D. S. Bastos; Armanda D. S. Bastos; Armanda D. S. Bastos; Sonja Matthee; Cory A. Gall; Jeanette Wentzel; Jeanette Wentzel; et al. (Frontiers in Cellular and Infection Microbiology)
The Bushbuckridge-East community in Mpumalanga Province, South Africa is bordered by nature reserves, including the Manyeleti Game Reserve. Murid rodents are prevalent in both Manyeleti and communal rangelands adjoining the community households. Although rodents are reservoir hosts for a broad range of viral, bacterial and parasitic pathogens, the rodent microbial diversity and transmission of zoonotic agents to humans in the community is understudied. In this study we investigated bacterial diversity in wild and commensal rodents sampled from different habitats. The 16S rRNA gene was amplified from DNA extracted from the blood of 24 wild Mastomys and one Steatomys sp. and subjected to PacBio circular consensus sequencing. As Bartonella species were dominant in the blood microbiome, gltA gene characterization was performed to delineate species. Rodents sampled from peri-urban and communal rangelands had higher proportions of Bartonella spp. [Hlalakahle (77.7%), Gottenburg (47.8%), Tlhavekisa (83.8%)] compared to those from the protected habitat (43.8%). Ehrlichia spp., Anaplasma spp., and Coxiella burnetii were detected at <1% of the sequence reads. Conventional PCR and sequencing validated the detection of Bartonella spp. with the first confirmation of Bartonella mastomydis infection in Mastomys in South Africa. Additionally, 317 mites, 90 fleas, 10 ticks and eight lice were collected from the rodents, providing evidence of possible vectors of the organisms detected. The detection of zoonotic agents in rodents in Bushbuckridge-East community, together with prior serological confirmation of Bartonella and Coxiella in non-malarial acute febrile patients from this community, highlights the possible risks that commensal rodents pose to human health.